The Cellular Environment Affects Monomeric α-Synuclein Structure. Issue 5 (May 2019) - Stephens, Amberley D.; Zacharopoulou, Maria; Kaminski Schierle, Gabriele S.
Abstract : The presynaptic protein α-synuclein (aSyn) is an 'intrinsically disordered protein' that is highly dynamic in conformation. Transient intramolecular interactions between its charged N and C termini, and between its hydrophobic region and the C terminus, prevent self-association. These interactions inhibit the formation of insoluble inclusions, which are the pathological hallmark of Parkinson's disease and many other synucleinopathies. This review discusses how these intramolecular interactions are influenced by the specific environment aSyn is in. We discuss how charge, pH, calcium, and salt affect the physiological structure of monomeric aSyn, and how they may favour the formation of toxic structures. The more we understand the dynamic conformations of aSyn, the better we can design desperately needed therapeutics to prevent disease progression. Highlights: aSyn is a highly dynamic, intrinsically disordered protein that populates an ensemble of different conformations in its functional, monomeric form. Functional, monomeric aSyn structure is stabilised by transient electrostatic and hydrophobic tertiary long-range interactions. Post-translational modifications (PTMs), truncation, and the local cellular environment, such as pH and ion content, can influence monomeric aSyn structure. A disruption of monomeric aSyn structure can bias the protein population towards aggregation-prone conformations, leading to the formation of amyloid fibrils. The structure of monomeric aSyn can imprint into fibril morphology and lead to the formation of different aSyn strains. Different aSyn fibril strains have been shown to lead to different levels of toxicity and may influence pathophysiology.